Evaluation of Landsat 8 imagery capability to estimate chlorophyll-a concentrations using spatially and temporally different data - Wijaya, Devy Risky Panji; Haribowo, Riyanto; Ball, James E. (Fakultas Teknik Universitas Brawijaya, 2023)
Water quality has been one of the major issues in water resources. A water quality monitoring program should be performed regularly. However, this program requires numerous resources and efforts, especially using a direct measurement method. An alternative should be carried out to minimise the issues. Landsat 8 (L8) can be the alternative. Water clarity is one of the essential water parameters affecting sunlight’s ability to penetrate water and engage photosynthesis. Algae is vital in photosynthesis and usually indicated as chlorophyll-a (chl-a). Several studies present that L8 is adequate to estimate chl-a concentrations as it provides high-accuracy results. This paper will generate a new model using data from different places and compare it with other chl-a models from previous studies by their capabilities to estimate chl-a concentrations. The results indicate that the generated model cannot provide consistent and precise estimations in different places and times, although it has a “good” R2 value at 0.7245 from the regression analysis for model generation. The same results arise from other models that cannot reasonably estimate chl-a concentrations.